Chromatic Characteristics of Sediments in Zhifu Loess Section of Yantai during the Last Interglacial Period and Its Paleoenvironmental Significance - Du Lan; Li Zhiwen; Du Dingding; Li Wubiao; Wang Zhigang; Ma Zeyuan; Zhan Jiangzhen (Redai dili, 2021)
Color is a vital characteristic of soil. It is also an important index to reveal the sedimentary environment and climate change of soil in a certain period. A quantitative description of color by the CIELAB color system can effectively avoid the significant influence of the human visual system on color perception. Additionally, it can be more intuitively used in the study of stratigraphic correlation, mineral content, and environmental change, and can help in explaining the changes in material sources and paleoclimate environment and revealing the remarkable characteristics of climate change during periodic glacial and interglacial periods. There are several loess-paleosol sedimentary sequences in the north of the Shandong Peninsula that contain abundant paleoenvironmental information. This study considered a typical section in the Zhifu District of Yantai City as a research object to explore the climate change characteristics of the northern Shandong Peninsula during specific periods. A chronological framework was built by collecting samples, dividing strata, and optically-stimulated luminescence dating, Moreover, the chromaticity was measured, the characteristics of chromaticity changing with section depth was analyzed, and the climate characteristics and change law of the last interglacial period was discussed. The results showed that 1) the bottom age of the profile was 124.9 ka, while the top age was approximately 62.85 ka, indicating that the main body belongs to the last interglacial deposit. The stratigraphic age-depth framework was constructed based on the piecewise sedimentation rate interpolation method, with a significant correlation between age and depth. This indicates that the new and old relationships between stratigraphic age and sequence are consistent, with no sedimentary fault or stratigraphic inversion. The chromaticity parameter results showed that the average value of L* was 52.13, which is higher in the loess layer than that of the paleosol layer; its high value indicated cold and dry climate conditions. The average values of a*, b*, C*, and h* were 11.18, 25.03, 27.43, and 0.421, respectively, indicating that the paleosol layer is higher than the loess layer; its high value indicated warm and humid climate conditions. A correlation analysis was carried out on the chromaticity parameters, indicating a significant correlation between L* and a* and between a* and b*, where a* and b* are controlled by the same substance and are the main factors affecting L*. 2) The following results were obtained by comparing the color saturation, hue angle, magnetic susceptibility of Chaona loess, and deep-sea oxygen isotopes. The chromaticity parameters showed three cycles of alternating peaks and valleys in the vertical direction of the profile. Their variation trend reflected the climate change characteristics of the last interglacial period, which was dominated by a summer monsoon, with a warm and humid climate, and more precipitation (MIS5e: 118.5‒124.9 ka). Subsequently, the intensity of the summer monsoon wind weakened, the intensity of the winter monsoon wind increased, and the air temperature dropped (MIS5d: 105.2‒118.5 ka), with the climate becoming hot and humid (MIS5c: 94.7‒105.2 ka). The monsoon intensity increased, and the temperature dropped (MIS5b: 83.4‒94.7 ka), becoming warm and humid (MIS5a: 70.18‒83.4 ka) and finally dry and cold (MIS 4: 62.85‒70.18 ka).